1986
DOI: 10.1111/j.1476-5381.1986.tb10164.x
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of motor behaviours in groups of rats distinguished by their climbing response to apomorphine

Abstract: Administration of apomorphine hydrochloride (0.5 mg kg−1 s.c.) to adult male or female Wistar rats previously acclimatized to the test environment induced climbing behaviour in approximately 50% of animals examined. The proportion of animals climbing was related to age, being maximal at 8–9 weeks. Those animals showing an initial climbing response to apomorphine (0.5 mg kg−1 s.c), climbed when challenged with this dose of apomorphine on subsequent occasions. In ‘climbing’ animals the intensity of response was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

1987
1987
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 15 publications
(18 reference statements)
0
10
0
Order By: Relevance
“…In a recent study, however, no difference was found between the classical neuroleptics haloperidol and chlorpromazine and the atypical neuroleptic thioridazine (Ljungberg and Ungerstedt 1985). Furthermore, the difficulty of this and other models using apomorphine to induce a behaviour is that the response of individual animals to apomorphine can vary greatly (Davis et al 1986). …”
Section: Discussionmentioning
confidence: 99%
“…In a recent study, however, no difference was found between the classical neuroleptics haloperidol and chlorpromazine and the atypical neuroleptic thioridazine (Ljungberg and Ungerstedt 1985). Furthermore, the difficulty of this and other models using apomorphine to induce a behaviour is that the response of individual animals to apomorphine can vary greatly (Davis et al 1986). …”
Section: Discussionmentioning
confidence: 99%
“…Rupniak et al (1983) found that purposeless chewing could be induced in rats with physostigmine 0.5 mg/kg. Davis et al (1986) found that apomorphine-induced stereotyped behaviours in rats over the dose range 0.03 1.0 mg/kg SC. Secoverine antagonised oxotremorineinduced analgesia in mice, with an EDso value of 7 mg/kg IP (Zwagemaakers and Claasen 1980).…”
Section: -Ht Antagonistsmentioning
confidence: 98%
“…Effect of EOPG on apomorphine-induced climbing test. The method described by Davis et al (1986) was adopted with minor modification. The following scoring system was employed: 0 ¼all paws on cage floor; 1 ¼two paws placed on the side of the cage; 2¼ all paws off floor; 3 animal climbed and remain on the wall.…”
Section: Assessment Scoresmentioning
confidence: 99%